Entrained theta oscillations guide perception of subsequent speech: behavioural evidence from rate normalisation. Issue 8 (14th September 2018) - Bosker, Hans Rutger; Ghitza, Oded
ABSTRACT: This psychoacoustic study provides behavioural evidence that neural entrainment in the theta range (3–9 Hz) causally shapes speech perception. Adopting the "rate normalization" paradigm (presenting compressed carrier sentences followed by uncompressed target words), we show that uniform compression of a speech carrier to syllable rates inside the theta range influences perception of subsequent uncompressed targets, but compression outside theta range does not. However, the influence of carriers – compressed outside theta range – on target perception is salvaged when carriers are "repackaged" to have a packet rate inside theta. This suggests that the brain can only successfully entrain to syllable/packet rates within theta range, with a causal influence on the perception of subsequent speech, in line with recent neuroimaging data. Thus, this study points to a central role for sustained theta entrainment in rate normalisation and contributes to our understanding of the functional role of brain oscillations in speech perception.